Accuracy of estimated fetal weight using ultrasound at term in pregnant women diagnosed with gestational and pre-gestational diabetes at Groote Schuur Hospital - Venter, Mareli (Department of Obstetrics and Gynaecology, 2019)
Background The incidence of diabetes is rising globally. Similarly, there has also been a rise in the incidence of diabetes in pregnancy, both pre-gestational as well as gestational. These patients are at risk of multiple perinatal complications, including macrosomia. There is an increased risk of perinatal complications with a fetal weight at birth of more than 4 000 g, especially if macrosomia occurs in the context of diabetes. In order to predict fetal macrosomia, fetal weight estimation remains an important component of antenatal surveillance. Despite the relative inaccuracy of ultrasound fetal weight estimation, the current National Institute for Health and Care Excellence (NICE) guideline on the care of diabetic patients, recommends offering 4 weekly ultrasound scans from 28 to 36 weeks to assess fetal growth and wellbeing. In addition, the Western Cape guidelines recommend offering an elective caesarean section to diabetic patients with an estimated fetal weight of 4 000 g or more at term with a fetal abdominal circumference greater than the 90th percentile. This practice has subsequently resulted in a large number of caesarean deliveries performed to prevent fetal and maternal complications related to presumed macrosomia. Objectives The aim of this study was to assess the accuracy of ultrasound fetal weight estimation performed in diabetic women at term, as well as to determine the incidence of macrosomia in the study population and the accuracy of ultrasound identification of macrosomia. Methods A retrospective audit was undertaken in women who attended antenatal services at Groote Schuur Hospital (GSH). This study reviewed women with an abnormal glucose tolerance test (GTT) during pregnancy or with known diabetes preceding pregnancy attending GSH during a 12-month period were included. Women with a singleton pregnancy at 36 weeks or more that underwent a documented ultrasound for fetal weight estimation within 7 days of delivery were included in this audit. Results A total of 97 women in the study population met the inclusions criteria. Seventy patients (72%) had gestational diabetes and 22 (18%) had pre-gestational diabetes. Ultrasound weight estimations were accurate to within 10% of birth weight in 70,1% of all patients. Eleven (11,3%) patients had macrosomic (> 4 000 g) babies. In these patients only 54,5% of fetal weight estimations were accurate to within 10% of birth weight. Ultrasound for detection of macrosomia had a sensitivity of 58,3% (CI: 36-82%) and a specificity of 96,5% (CI: 93-99%). Conclusion The accuracy of ultrasound fetal weight estimation performed in diabetic patients at GSH appears similar to that of other international studies. Ultrasound estimations become increasingly inaccurate in extremes of fetal weight. One in four fetal weight estimations had an estimation error of > 10% with a tendency towards underestimation in macrosomic fetuses. Ultrasound fetal weight estimation as a predictor for fetal macrosomia should therefore remain under scrutiny, especially in the context of the high perinatal morbidity associated with macrosomia and shoulder dystocia as well as the rising litigation related to birth complications.